2017
DOI: 10.1007/s11745-017-4249-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fabp1/Scp2/Scpx Ablation on Whole Body and Hepatic Phenotype of Phytol‐Fed Male Mice

Abstract: Liver fatty acid binding protein (Fabp1) and sterol carrier protein-2/sterol carrier protein-x (SCP-2/SCP-x) genes encode proteins that enhance hepatic uptake, cytosolic transport, and peroxisomal oxidation of toxic branched-chain fatty acids derived from dietary phytol. Since male wild-type (WT) mice express markedly higher levels of these proteins than females, the impact of ablating both genes (TKO) was examined in phytol-fed males. In WT males, high phytol diet alone had little impact on whole body weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 82 publications
(158 reference statements)
0
11
0
Order By: Relevance
“…Taken together, these findings showed that the greater hepatic accumulation of phytanic acid in phytol-fed WT females than males correlated with the females' markedly lower expression of FABP1, SCP-2, and SCP-x than WT males (60,61), perhaps analogous to partial "knock-down" of these proteins involved in phytol metabolism. This possibility was supported by the finding that complete ablation of all three proteins (i.e., TKO) resulted in a much greater quantitative loss of FABP1, SCP-2, and SCP-x in male than female mice and, thereby correspondingly, in greater increase in phytanic acid accumulation in phytol-fed TKO males than their female counterparts.…”
Section: Tko Induces Hepatic Accumulation Of Phytol Metabolite Producmentioning
confidence: 73%
See 2 more Smart Citations
“…Taken together, these findings showed that the greater hepatic accumulation of phytanic acid in phytol-fed WT females than males correlated with the females' markedly lower expression of FABP1, SCP-2, and SCP-x than WT males (60,61), perhaps analogous to partial "knock-down" of these proteins involved in phytol metabolism. This possibility was supported by the finding that complete ablation of all three proteins (i.e., TKO) resulted in a much greater quantitative loss of FABP1, SCP-2, and SCP-x in male than female mice and, thereby correspondingly, in greater increase in phytanic acid accumulation in phytol-fed TKO males than their female counterparts.…”
Section: Tko Induces Hepatic Accumulation Of Phytol Metabolite Producmentioning
confidence: 73%
“…Because nonalcoholic fatty liver disease (NAFLD) is characterized by hepatic lipid accumulation, these studies suggested that the lower hepatic expression of FABP1, SCP-2, and SCP-x in WT females may make females more susceptible to NAFLD, correlating with high-fat-induced NAFLD in some strains of female (73), but not male, mice (74), as well as with the higher prevalence of NAFLD in women (74,75). Furthermore, phytol-diet made WT mice less susceptible to hepatic triacylglyceride accumulation, more so males than females and correlated with WT females having lower hepatic expression of FABP1, SCP-2, and SCP-x than WT males (60,61).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…iii) TKO results in different metabolic patterns between male and female mice due to sex differences in FABP1 and SCP-2/SCP-x expression as well as to Fabp1 and Scp2/Scp-x having different metabolic functions in health and disease. For example, phytol (a normal dietary constituent derived from the side chain of chlorophyll) markedly decreases body weight gain and increases weight loss more so in female than male WT mice [8,57,79]. This difference has been attributed to the lower expression of the protein products of the Fabp1 and/or Scp2/Scp-x genes, both of which are involved in phytol metabolism [5,8,75,107,113].…”
Section: Discussionmentioning
confidence: 99%
“…This mouse strain is available from The Jackson Laboratory (Item # 005304). TKO mice were developed as described (Landrock et al, ; Milligan et al, ; Storey et al, ). TKO mice have been deposited with and are available from The Jackson Laboratory (Bar Harbor, ME, USA).…”
Section: Methodsmentioning
confidence: 99%